Correction: The Murine Coronavirus Hemagglutinin-esterase Receptor-binding Site: A Major Shift in Ligand Specificity through Modest Changes in Architecture - Langereis, Martijn A.; Zeng, Qinghong; Heesters, Balthasar A.; Huizinga, Eric G.; de Groot, Raoul J. (PLOS Pathogens, 2012)
null